Legal Analysis of Attempt on the Life of Internal Affairs Officer as the Body of Criminal Offence - ISSABAYEV, Chingiz A.; YESKENDIROV, Aidos A.; SHAYAKHMETOVA, Zhanna B.; BEGALIYEV, Bakhytbek A.; KHAMMETOVA, Zhanargul A. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).21, 2020)
Disorganized crime impact on the society is provided by criminal pressure on law enforcement officials – from engagement in criminal networks, bribery, blackmail to their liquidation. Social danger of the offences studied is that it threatens the life of internal affairs officer to prevent him from professional duties for the law enforcement, intentionally destabilizes normal operation of public authorities, and undermines their authority in the public’s mind. The purpose of the article was to analyze the types and motives of attempts on an employee of internal affairs bodies from a legal point of view. To achieve the purpose, the opinions of other researchers who studied this problem were examined, as well as legal documents regulating crimes committed against employees of internal affairs bodies. It was noted inconsistencies in the evaluation of sanction measures against perpetrators responsible for offences provided for by p. 2, part 2, article 99 and part 1, article 380-1 of the Criminal Code of Kazakhstan. It was concluded that the strengthening of criminal liability will significantly affect the status of crime situation, enhance the government authority and strengthen overall prevention in the country.